COMMUNITY NEWSBOARD AS A MICRO-MEDIUM FOR DEVELOPMENT COMMUNICATION - Alesna, Wolfreda T. (Annals of Tropical Research, 1979)
The study was conducted in Igang and San Isidro, both rice farming barrios in Baybay, Leyte, to measure the effectiveness of community newsboard (CN) as a micro-medium for development communication using randomly selected literate respondents. The pretest-posttest-control group design was used. Igang was selected as the treatment barrio and San Isidro as the control. Four of the seven variables (sex, frequency of exposure, perceived relevance of the CN messages and acceptability of the CN as a medium) considered in this study had significant relationships with gain in knowledge. Male respondents had significantly gained more knowledge about the information written on the CN than the female respondents. All the respondents who have read the CN unanimously perceived the CN messages as relevant and also accepted CN as a channel for disseminating farm and other developmental information. They have also significantly gained knowledge about the information written on it.